Peran Media Sosial dalam Pembentukan Identitas : Perspektif Cultural Studies - Sari, Reka Purnama; Trenggono, Nanang; Aryanti, Nina Yudha; Ashaf, Abdul Firman; Kartika, Tina (Innovative: Journal Of Social Science Research, 2025)
This study addresses the central issue of how social media plays a role in the process of identity formation amid the currents of globalization and digitalization. The main objective of this research is to understand how social media influences the identity formation process and to examine how Cultural Studies theory explains the relationship between social media, representation, and identity construction. This study employs a qualitative method with a Cultural Studies perspective to provide a deeper understanding of the dynamics of identity formation in the digital era. The findings indicate that social media in the digital age has become a new cultural space that plays a significant role in the identity formation process. Beyond functioning as a communication tool, social media serves as a site of representation, expression, and the ongoing construction of identity meaning. It can be seen as a contested arena of cultural identity for individuals on one hand, a medium for self expression and affirmation, and on the other, a force that potentially homogenizes identity through global popular culture and the logic of the digital marketplace.